Carotenoids and xanthophyll esters of yellow and red nance fruits (Byrsonima crassifolia (L.) Kunth) from Costa Rica. (September 2018) - Irías-Mata, Andrea; Jiménez, Víctor M.; Steingass, Christof Björn; Schweiggert, Ralf M.; Carle, Reinhold; Esquivel, Patricia
Abstract: Carotenoid profiles, by means of HPLC-PDA-MS n, and CIE-L*C*h° colour values of yellow and red nance fruits from Costa Rica were elucidated. Among 16 carotenoids detected, (all- E )-lutein was the most abundant accounting for >80% of the total carotenoids, followed by (all- E )-zeaxanthin (9–11%) and (all- E )-β-carotene (2–9%). Minor constituents were ( Z )-isomers of lutein and β-carotene, as well as diverse lutein diesters. Among the esters, lutein dimyristate was the most abundant as substantiated by the comparison with a marigold flower extract. Total carotenoids in the peel (616.2 μg/100 g of FW in yellow nance and 174.2 μg/100 g of FW in red nance) were higher than in the pulp (39.4 μg/100 g of FW in yellow nance and 31.4 μg/100 g of FW in red nance). Since carotenoid profiles of yellow and red varieties were qualitatively similar, although the colour values showed significant differences (77.2 and 88.6 h° in peel and pulp of yellow nance, versus 32.7 and 67.3 h° in peel and pulp of red nance, respectively), pigments other than carotenoids may impart the colour of red nance. High lutein content renders nance fruit as a nutritionally relevant source of this micronutrient. Graphical abstract: Unlabelled Image Highlights: Carotenoids of red nance fruits are reported for the first time. Distribution of carotenoids within peel and pulp of nance fruits was first-time analysed. Identification of 16 carotenoids by HPLC-PDA-MS n reveals lutein as the most abundant. Identification of lutein diesters was achieved by comparison with a marigold flower extract. Pigments other than carotenoids may define the colour of red nance fruits.